Analysis of Marketing Mix Strategies with 4P Method Classification (Product, Price, Place, & Promotion) on the Marketing Growth of Marine Paint Products at PT. NIPSEA Panit & Chemicals – Surabaya Period 2020-2022 - Wardhana, I Kadek Yushak; Jufriyanto, Moh; Rizqi, Ahmad Wasiur (Jurnal Teknik Industri Terintegrasi (JUTIN), 2023)
This study delves into the analysis of Marketing Mix Strategies using the 4P Method Classification (PRODUCT, PRICE, PLACE, & PROMOTION) and its impact on the marketing growth of Marine Paint Products at PT. NIPSEA PAINT & CHEMICALS, Surabaya, during the period from 2020 to 2022. The research focuses on the strategies employed to enhance the market presence and profitability of marine paint products. Through an in-depth investigation, the study evaluates the effectiveness of product design, pricing strategies, distribution channels, and promotional campaigns in driving growth and success within the marine paint industry. The findings of this research aim to provide valuable insights for marketers and business professionals seeking to optimize their marketing strategies in the marine paint sector, ultimately contributing to improved market performance and competitiveness.